FOUR DECADES OF CROPS RESEARCH AND TEACHING AT OBAFEMI AWOLOWO UNIVERSITY - FAKOREDE, M. A. B. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The department of plant science became an academic and administrative entity within the University in the 1966/67 session. Since then, the department has been putting human and material resources in place for teaching of, and research into, crop production, improvement and protection. During the 40 years under review in this report, the department produced many undergraduate and graduate students in the different subject-matter areas; including plant breeding and genetics, agronomy, agroclimatology and crop physiology, seed production and physiology, entomology, plant pathology (Mycology and Bacteriology), Nematology, virology and weed science. The department made major breakthrough in research in these areas and developed several high-yielding varieties of cowpea, maize and tomato that were released its capacity in research and teaching in the more contemporary areas of Seed Science and Biotechnology.